Retrospective analysis on the immunopotentiating mechanism of an emulsion-based vaccine adjuvant on human antigen presenting cells - Bonam, Srinivasa Reddy; Platenburg, Peter Paul; Bayry, Jagadeesh (Frontiers in Immunology, 2023)
We retrospectively analyzed the immunopotentiating mechanism of an oil-in-water (O/W) emulsion-based vaccine adjuvant LiteVaxTM Adjuvant (LVA) that contains CMS (Maltose 4’-monosulphate 1,2,3,6,2’,3’,6’-heptadecanoic acid ester), squalane, Tween 80 in phosphate buffered saline. Despite being effective in animal models, the immunological mechanisms by which LVA exerts adjuvant function are not known. As dendritic cells (DC) are key for initiating and propagating the immune response, we have investigated the effect of LVA and of its components on the DC function. We show that CMS but not LVA significantly enhances the expression of DC activation-associated markers, cytokine secretion, and CD4+ T cell responses. On the other hand, CMS ZERO [CFASE, a mixture of non-sulphated sucrose fatty acid esters (ZERO)], used as a control, had no such activity. Our data identified the unique nature of CMS in LVA, and propose that LVA acts as a delivery system, and CMS acts as an immunostimulatory agent.